Acute kidney injury in Turkey: epidemiological characteristics, etiology, clinical course, and prognosis - Gursu, Meltem; Yegenaga, Itir; Tuglular, Serhan; Dursun, Belda; Bek, Sibel Gokcay; Bardak, Simge; Tonbul, Halil Zeki (Bmc, 2022)
Background This study aimed to evaluate the etiologies, comorbidities, and outcomes of acute kidney injury (AKI) in Turkey and determine any potential differences among different geographical parts of the country. Methods This prospective observational study was conducted by the Acute Kidney Injury Working Group of the Turkish Society of Nephrology. Demographical and clinical data of patients with AKI at the time of diagnosis and at the 1(st) week and 1(st), 3(rd), and 6(th) months of diagnosis were evaluated to determine patient and renal survival and factors associated with patient prognosis. Results A total of 776 patients were included (54.7% male, median age: 67 years). Prerenal etiologies, including dehydration, heart failure, and sepsis, were more frequent than other etiologies. 58.9% of the patients had at least one renal etiology, with nephrotoxic agent exposure as the most common etiology. The etiologic factors were mostly similar throughout the country. 33.6% of the patients needed kidney replacement therapy. At the 6(th) month of diagnosis, 29.5% of the patients had complete recovery; 34.1% had partial recovery; 9.5% developed end-stage kidney disease; and 24.1% died. The mortality rate was higher in the patients from the Eastern Anatolian region; those admitted to the intensive care unit; those with prerenal, renal, and postrenal etiologies together, stage 3 AKI, sepsis, cirrhosis, heart failure, and malignancy; those who need kidney replacement therapy; and those without chronic kidney disease than in the other patients. Conclusion Physicians managing patients with AKI should be alert against dehydration, heart failure, sepsis, and nephrotoxic agent exposure. Understanding the characteristics and outcomes of patients with AKI in their countries would help prevent AKI and improve treatment strategies.
Keywords: Acute kidney injury; Etiology; Kidney replacement therapy; Survival